Perancangan Ulang Identitas Visual Dan Media Promosi Hamta.Ku Petshop Untuk Meningkatkan Brand Awareness - Feren Velincia Sanjaya S; Michel Sutedja (DEKAVE : Jurnal Desain Komunikasi Visual, 2024)
The design of this thesis work was made with the aim of producing a new visual identity design to improve brand identity, differentiate itself from competitors, and adjust to the changing needs of the target market. The redesign of Hamta.ku Petshop also allows the improvement of the weaknesses of the old identity, this strengthening the image and competitiveness of Hamta.ku Petshop in the market. The research method used in this design is a qualitative method with interview data collection, and collecting data on public views through distributing questionnaires, as well as making direct observations of Hamta.ku and other Petshop.The result of this design is a logo design that has a visual that suits the target market. By creating an attractive visual using colours and characters as its identitykey word: Petshop, Logo, brand identity, Pets, media promotion